Listening Comprehension and Text Representation of Animated Videos in Arabic Courses: A Case Study in Indonesian Higher Education - Andi Hazrah Nurhaliza Ibrahim; Zamakhsari Zamakhsari; Zainal Arifin Ahmad (Abjadia : International Journal of Education, 2026)
This study aims to describe the quality of literal comprehension that measured through transcript accuracy and reflective comprehension that measured through istinbāṭ or magzā among first-semester Arabic Language Education students at Sunan Kalijaga State Islamic University Yogyakarta after watching animated videos in the Al-Istimā' course. Using a qualitative case study approach, data were collected from 37 students through written assignments via Google Form (30 of which were complete and analyzed), followed by semi-structured interviews with five selected participants. The findings reveal that students' literal comprehension remains low, 57% struggled with literal transcription, falling into the “adequate” category due to difficulties in content accuracy, narrative completeness, and Arabic grammar. In contrast, students' reflective comprehension was significantly higher, with 50% demonstrated strong reflective comprehension, achieving a 'very accurate' score in formulating magzā, indicating that universal values and prior knowledge support inferential understanding. Notably, the relationship between literal and reflective comprehension was non-linear: some students with low transcript accuracy produced high-quality istinbāṭ, and vice versa. These findings suggest that listening comprehension is multidimensional and that evaluating Istimā' purely through literal measures provides an incomplete picture of student ability. The study contributes theoretically to Arabic listening pedagogy and practically to the design of integrated listening writing reflective tasks.